Delay discounting as impaired valuation: Delayed rewards in an animal obesity model. Issue 2 (20th September 2017) - Jarmolowicz, David P.; Hudnall, Jennifer L.; Hale, Luanne; Fowler, Stephen C.; Bortolato, Marco; Lemley, Shea M.; Sofis, Michael J.
Abstract : Obesity is a major public health problem, which, like many forms of addiction, is associated with an elevated tendency to choose smaller immediate rather than larger delayed rewards, a response pattern often referred to as excessive delay discounting. Although some accounts of delay discounting conceptualize this process as impulsivity (placing the emphasis on overvaluing the smaller immediate reward), others have conceptualized delay discounting as an executive function (placing the emphasis on delayed rewards failing to retain their value). The present experiments used a popular animal model of obesity that has been shown to discount delayed rewards at elevated rates (i.e., obese Zucker rats) to test two predictions that conceptualize delay discounting as executive function. In the first experiment, acquisition of lever pressing with delayed rewards was compared in obese versus lean Zucker rats. Contrary to predictions based on delay discounting as executive function, obese Zucker rats learned to press the lever more quickly than controls. In the second experiment, progressive ratio breakpoints (a measure of reward efficacy) with delayed rewards were compared in obese versus lean Zucker rats. Contrary to the notion that obese rats fail to value delayed rewards, the obese Zucker rats' breakpoints were (at least) as high as those of the lean Zucker rats.